Modification of Magnesium Oxide from Bittern Waste with Strontium Oxide for Palm Oil Transesterification Process - Qoyyima, Diana; Jumaeri, Jumaeri (Universitas Negeri Semarang, 2021)
Bittern has a high magnesium content, so that it can be used as a catalyst in the production of biodiesel through the transesterification process. MgO catalyst has a relatively low basicity, so it is necessary to add metal oxides such as SrO. This study aims to determine the characteristics and catalytic effectiveness of the SrO/MgO catalyst in the transesterification process of palm oil using GC and GCMS tests. Modification of SrO on the MgO catalyst was carried out using the impregnation method with a ratio of 1:3. The presence of SrO diffraction peaks on XRD analysis showed that SrO agglomerated on the MgO surface, this can be attributed to the morphology of the spheres which are homogeneously agglomerated. The result of basicity analysis shows that the addition of SrO can increase the number of moles of base of MgO. In the palm oil transesterification process using an SrO/MgO catalyst, the methyl ester conversion increased by 47.17% at the optimal reaction time of 2 hours, while the MgO catalyst only resulted in a conversion of 2.35%. Based on the results of the study, it was found that the addition of SrO could increase the catalytic effectiveness of MgO.